Case report: Epithelioid inflammatory myofibroblastic sarcoma treated with an ALK TKI ensartinib - Li, Mengmeng; Xing, Ruyue; Huang, Jiuyan; Shi, Chao; Wei, Chunhua; Wang, Huijuan (Frontiers in Oncology, 2023)
Epithelioid inflammatory myofibroblastic sarcoma (EIMS) is an aggressive variant of inflammatory myofibroblastic tumor (IMT) harboring anaplastic lymphoma kinase (ALK) gene fusions and is associated with high risk of local recurrence and poor prognosis. Despite no standard therapy for EIMS, ALK tyrosine kinase inhibitors (TKIs) are recommended for those harboring ALK gene rearrangements. Herein, we describe a case of a 31-year-old male who presented with an abdominal mass. The patient suffered from recurrence and multiple metastases 2 months after surgery. Ensartinib was administered and RANBP2-ALK fusion was detected. The patient continues to be alive with partial response for 4 months and has no recurrence. Although EIMS has a poor prognosis, this study provided a successful case with sustained response of targeted therapy.